ERAN BPR JATIM DALAM PENINGKATAN PENDAPATAN UMKM DI KOTA SURABAYA GUNA MENCAPAI VISI MISI GUBERNUR JATIM - Setyono, Vicky Indarto; Ratnawati, Tri (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
BPR Jatim is a bank owned by the East Java Provincial Government and Regency / City Governments throughout East Java. In its role as an intermediary institution and supporting government programs, BPR East Java always strives to increase credit distribution to the real sector, especially micro, small and medium enterprises by offering products tailored to customer needs. This is done because there are still many MSMEs in the city of Surabaya who are experiencing capital difficulties. The limited capital owned by MSMEs will affect the development of MSMEs. BPR Jatim Kota Surabaya has 1,977 customers. This study aims to analyze the role of BPR East Java in increasing the income of MSMEs in the city of Surabaya. The method used in this research is descriptive qualitative. Data were collected using interview, observation and documentation methods. The subjects in this study were customers and employees of BPR Jatim. Then the object is the role of the East Java BPR. The results showed that the East Java BPR plays a very important role in the development of MSMEs in the city of Surabaya. BPR Jatim offers various types of credit products tailored to customer needs. Among the existing types of credit, 70% of East Java BPR customers take special loans. BPR Jatim also provides convenience in terms and procedures for applying for credit and provides the best service for its customers. East Java BPR customers have increased every month. All informants said that their business had developed after receiving credit from the East Java BPR. This development is indicated by an increase in income, additional workforce and more advanced business units. Keywords: East Java BPR, Income, UMKM